Analisis Faktor Rendahnya Motivasi Belajar Mahasiswa - Sahib, Abdul (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2020)
This study aims to determine the factors that cause low motivation to learn IAIN Curup students, especially in the fourth semester Islamic Education Study Program. The method used in this paper is a qualitative method, data collected from observations, documentation and interviews with 30 respondents . The results of the study found 3 important parts that affect student interest in learning, namely the preparation and planning of learning by students and lecturers; secondly the evaluation of lecture implementation and thirdly the lecture obstacles experienced by students. There are several factors that cause students to have low motivation to learn, namely: 1) economic factors, which cause a lack of concentration in learning, because they require them to work while in college, 2) alumni absorption factors in low employment, making students doubt the future after becoming undergraduate, 3) the educational background factors of the majority of students from public schools, causing difficulties in attending Islamic-based courses. Conclusions, It needs careful planning in preparing the curriculum, Implementation of the curriculum is really done, Need to increase student motivation, evaluation and assessment of students is really carried out according to existing provisions, Obstacles experienced in each implementation of the task is not something to be avoided but he was demanded to find a solution so that the next process is not hampered. Keywords: PAI Learning, STAIN Students, Learning Motivation